2014
DOI: 10.1002/hbm.22540
|View full text |Cite
|
Sign up to set email alerts
|

Reward anticipation in the adolescent and aging brain

Abstract: Processing of reward is the basis of adaptive behavior of the human being. Neural correlates of reward processing seem to be influenced by developmental changes from adolescence to late adulthood. The aim of this study is to uncover these neural correlates during a slot machine gambling task across the lifespan. Therefore, we used functional magnetic resonance imaging to investigate 102 volunteers in three different age groups: 34 adolescents, 34 younger adults, and 34 older adults. We focused on the core rewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 64 publications
2
37
0
Order By: Relevance
“…Dissociating different features of the various reward paradigms, in addition to more studies of negative valence, will further clarify how these age-related neural changes impact behavior -- particularly risk-taking tendencies that can be ascribed to over-activity in reward processing networks. Notably, previous studies on adolescent reward processing have relied on studies of adult reward processing (Liu et al, 2011) for guiding hypothesis testing and ROI analyses (e.g., Lorenz et al, 2014). Given the differences found here between adolescent and adult reward processing, this and similar meta-analyses of adolescent reward processing can guide hypothesis testing for future studies focusing on adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Dissociating different features of the various reward paradigms, in addition to more studies of negative valence, will further clarify how these age-related neural changes impact behavior -- particularly risk-taking tendencies that can be ascribed to over-activity in reward processing networks. Notably, previous studies on adolescent reward processing have relied on studies of adult reward processing (Liu et al, 2011) for guiding hypothesis testing and ROI analyses (e.g., Lorenz et al, 2014). Given the differences found here between adolescent and adult reward processing, this and similar meta-analyses of adolescent reward processing can guide hypothesis testing for future studies focusing on adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The caudate is another brain region in which abnormality is commonly reported in depressive disorder patients (Zhang et al, 2013). As a central part of the reward circuit, in contrast to the amygdala, the caudate is more often associated with the processing of rewards (Lorenz et al, 2014) and positive emotion (Haber and Knutson, 2010). A previous structural study in non-clinical participants reported that trait anhedonia is linked to volumetric reduction in the caudate (Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, most studies outline that it is precisely the transition from middle-age adulthood to older age (around 50 years-old) the critical phase with relevant adjustments and changes which can significantly affect the gambling habits, being the most relevant risk factors for GD some socio-demographical variations (e.g. employment retirement, financial disadvantages or social isolation) 50,51 , the age-related neurological vulnerabilities in the mechanisms related with behavioral regulation and diminished executive functioning typical of elderly [52][53][54] , and the physical and psychological unhealthy typical of the senior age (such as chronic medical conditions, limited mobility, anxiety or depression) 55 .…”
Section: Methodsmentioning
confidence: 99%